CONSUMER AWARENESS TOWARDS ECO FRIENDLY PRODUCTS IN TENKASI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACTCustomers want to buy green products as they become more environmentally concerned. Green goods are either environmentally friendly in and of themselves or manufactured in an environmentally friendly manner.People's need to drastically alter their lifestyles in order to slow global warming has made the issue of climate change contentious. Businesses have begun to switch to environmentally friendly marketing tactics in an effort to boost product value and sales. In order to increase customer awareness of green products